2002
DOI: 10.1210/me.2002-0058
|View full text |Cite
|
Sign up to set email alerts
|

Synaptosome-Associated Protein of 25 Kilodaltons Modulates Kv2.1 Voltage-Dependent K+ Channels in Neuroendocrine Islet β-Cells through an Interaction with the Channel N Terminus

Abstract: Insulin secretion is initiated by ionic events involving membrane depolarization and Ca(2+) entry, whereas exocytic SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) proteins mediate exocytosis itself. In the present study, we characterize the interaction of the SNARE protein SNAP-25 (synaptosome-associated protein of 25 kDa) with the beta-cell voltage-dependent K(+) channel Kv2.1. Expression of Kv2.1, SNAP-25, and syntaxin 1A was detected in human islet lysates by Western blot, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 33 publications
7
64
0
Order By: Relevance
“…Previous work had shown that these t-SNAREs can bind to and regulate the gating of Kv2.1. [15][16][17][18] However, since the gating of the delayed rectifier does not change with apoptosis, 2 the neurotoxin results, in concert with our trafficking experiments, are most consistent with the requirement of t-SNARE proteins for the membrane fusion required for insertion of new channels into the cell surface. This conclusion also is in accordance with the observations that overexpression of syntaxin in cell lines inhibits exocytosis 19 and Kv2.1 surface expression.…”
Section: Discussionsupporting
confidence: 79%
“…Previous work had shown that these t-SNAREs can bind to and regulate the gating of Kv2.1. [15][16][17][18] However, since the gating of the delayed rectifier does not change with apoptosis, 2 the neurotoxin results, in concert with our trafficking experiments, are most consistent with the requirement of t-SNARE proteins for the membrane fusion required for insertion of new channels into the cell surface. This conclusion also is in accordance with the observations that overexpression of syntaxin in cell lines inhibits exocytosis 19 and Kv2.1 surface expression.…”
Section: Discussionsupporting
confidence: 79%
“…Syx and SNAP Directly Bind Cytosolic Domains of Kv2.1-Previously, we have shown in an in vitro binding assay that Syx and SNAP bind to the Kv2.1 channel (14,28). In this study we carried out a more comprehensive in vitro binding assay to substantiate the physical interaction of the channel with these proteins.…”
Section: Resultsmentioning
confidence: 89%
“…Preparation of mRNAs was as described (23). DNAs of Kv2.1 fragments for production of GST fusion proteins were constructed as described before (14). Materials and enzymes for molecular biology were purchased from Roche Applied Science, Promega (Madison, WI), and MBI Fermentas (Vilnius, Lithuania).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations